2019
DOI: 10.1155/2019/1586328
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic Lymphoma, a Rare Entity in Bone Marrow with Unusual Immunophenotype and Challenging Differential Diagnosis

Abstract: Plasmablastic lymphoma (PBL) is an aggressive malignancy that usually occurs in the setting of immunosuppression. The immunohistochemical profile of PBL is that of terminally differentiated B lymphocytes. CD138, CD38, and MUM1 are usually immunopositive. However, pan B-cell markers such as CD20 and PAX-5 are usually negative.MYCrearrangement is the most commonly encountered genetic alteration, with immunoglobulin (IG), especially immunoglobulin heavy (IGH) chain, being the most frequent partner. We report a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…CD45 (leukocyte common antigen) is a receptor-linked protein tyrosine phosphatase expressed in all leukocytes. Positive CD-45 examination is seen in 97% of B cells and in 90% of cell lymphomas (Alikhan et al 2016, Al Shaarani et al 2019, King & Lam. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CD45 (leukocyte common antigen) is a receptor-linked protein tyrosine phosphatase expressed in all leukocytes. Positive CD-45 examination is seen in 97% of B cells and in 90% of cell lymphomas (Alikhan et al 2016, Al Shaarani et al 2019, King & Lam. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Reports with insufficient clinical information of the patients were excluded. The literature review revealed 105 cases of HIV‐associated oral PBL in 46 published manuscripts 1,3,7–37 …”
Section: Analysis Of the Literature Including A New Casementioning
confidence: 99%
“…The immunophenotype is similar to plasma cells: negative for CD45 with low/absent pan B-cell markers (CD20, CD79a and PAX5) and positive for plasma cell-associated markers (CD38, CD138 and MUM-1), with variable expression of immunoglobulins and negativity of bcl-6. Plasmablastic lymphoma showing aberrant expression of CD3 and CD411 or CD138 negativity12 has been described. C-myc rearrangements, particularly with translocation MYC-IGH (C-myc/immunoglobulin heavy chain), resembling Burkitt lymphoma, are cytogenetic abnormalities of note 7 9 10 13.…”
Section: Introductionmentioning
confidence: 99%
“…The most common location is the oral cavity1 3 4 7 9 10 and gastrointestinal tract,9 10 16 whereas the skin lesion has also been recorded 10 17. Bone marrow involvement is also encountered 12. It shows male predominance and the median age in the fourth and fifth decades of life.…”
Section: Introductionmentioning
confidence: 99%